FEMINISME DALAM NOVEL SAMAN KARYA AYU UTAMI DAN IMPLEMENTASINYA DALAM PEMBELAJARAN TEKS NOVEL KELAS XII SMA - Putri, Elvi Novrita; Asri, Yasnur (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is to describe and analyze the forms of feminism and their implementation in the learning of novel texts in class XII of high school. This type of research is qualitative research with descriptive methods. The data source in this study is Ayu Utami's Saman novel. The data in this study are words, phrases, clauses, and sentences that show the form of feminism in the novel. The subject of this research is the researcher himself with the help of other instruments in the form of a recording sheet. The data collection technique, which is reading and understanding Ayu Utami's Saman novel, conducts literature studies related to research problems, and searches and records data relating to research problems contained in the novel. The data validation technique uses triangulation techniques. The results of the study were found as participants. First, there are two forms of feminism in Ayu Utami's Saman novel, namely verbal and nonverbal forms. Verbal form is a form of the character's struggle through verbal utterances by the characters. And nonverbal forms are physical actions of characters. Second, the application of feminism in Ayu Utami's Saman novel in 2013 class XII high school text learning curriculum with basic competencies related to three aspects of assessment, namely the assessment of knowledge, attitudes, and skills.Â Kata Kunci: feminisme, pembelajaran teks novel